Digital Marketing dalam Menghadapi Persaingan Bisnis Sebuah Universitas di Era Digital: Kajian Konseptual - Fahmi Iqbal Firmananda; Jati, Putri Zulia; Lailatul Syifa Tanjung (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
Digital transformation has fundamentally changed the marketing strategies of higher education institutions, requiring universities to adapt to increasingly fierce competition. This article aims to conceptually examine the role of digital marketing in shaping institutional image and increasing interest in enrollment, with a focus on Universitas Pahlawan Tuanku Tambusai. The study was conducted through a qualitative descriptive conceptualization approach by reviewing literature and previous research results. The results of the study indicate that digital marketing makes a significant contribution to the formation of campus image through digital channels such as social media, websites, and visual content. As much as 57% of the data shows a strong correlation between digital marketing and institutional image, and 47% of the data shows a strong correlation with interest in enrollment. A consistent, interactive, and value-based digital communication strategy has been shown to strengthen brand awareness, increase audience engagement, and shape positive perceptions of the university. Therefore, digital marketing not only functions as a promotional tool, but also as a strategic instrument in building the competitiveness of higher education in the digital era.